دور تنمية رأس المال الاجتماعي في الترويج لخدمات المكتبات العامة دراسة ميدانية في المكتبات العامة التابعة لمديرية الثقافة في محافظة اللاذقية (Latakia University Journal - Economic and Legal Sciences Series, 2016)
يهدف البحث إلى دراسة العلاقة بين تنمية رأس المال الاجتماعي المتمثل بـ: التزام العاملين بأخلاقيات العمل, وبناء الثقة, وتنمية شبكات العلاقات الاجتماعية, واستثمار إمكانات المكتبة لتحسين خدمة المجتمع, وبين الترويج لنشاطات المكتبات العامة بين جمهور المستفيدين. اعتمد البحث المنهج الوصفي, وشمل مجتمع البحث جميع العاملين في المكتبات التابعة لمديرية الثقافة في محافظة اللاذقية, والبالغ عددهم تقريباً (154) عاملاً. ونظراً لصغر حجم مجتمع البحث تمّ استخدام طريقة الحصر الشامل, حيث تمّ توزيع (154) استبانة على العاملين, أعيد منها (141), وبنسبة استجابة بلغت (91.56%). وتوصل البحث إلى النتائج الآتية:*يوجد علاقة طردية وقوية ذات دلالة إحصائية بين التزام العاملين بأخلاقيات العمل في المكتبات العامة والترويج لنشاطاتها بين جمهور المستفيدين, حيث أنّ (66.3%) من التغيرات الحاصلة في الترويج لنشاطات المكتبات العامة بين جمهور المستفيدين يفسرها التزام العاملين بقيم وأخلاقيات العمل.*يوجد علاقة طردية ومقبولة ذات دلالة إحصائية بين بناء الثقة وتوطيد العلاقة بين مجتمع المكتبة العامة والترويج لنشاطاتها بين جمهور المستفيدين, حيث أنّ (57.2%) من التغيرات الحاصلة في الترويج لنشاطات المكتبات العامة بين جمهور المستفيدين يفسرها بناء الثقة وتوطيد العلاقة مع مجتمع المكتبة.*يوجد علاقة طردية ومقبولة ذات دلالة إحصائية بين تنمية شبكة العلاقات الاجتماعية في المكتبات العامة والترويج لنشاطاتها بين جمهور المستفيدين, حيث أنّ (52.3%) من التغيرات الحاصلة في الترويج لنشاطات المكتبات العامة بين جمهور المستفيدين يفسرها تنمية شبكة العلاقات الاجتماعية.*يوجد علاقة طردية ومقبولة ذات دلالة إحصائية بين تنمية استثمار إمكانات المكتبة العامة لتحسين خدمات المجتمع والترويج لنشاطاتها بين جمهور المستفيدين, حيث أنّ (49.1%) من التغيرات الحاصلة في الترويج لنشاطات المكتبات العامة بين جمهور المستفيدين يفسرها تنمية استثمار إمكانات المكتبة العامة لتحسين خدمات المجتمع.The research aims to study the relationship between social capital development of: a commitment of workers to the work value and ethic and trust building, and the development of networks of social relations, and investment potential of the library to improve the service of society, and the promotion of the activities of public libraries between public beneficiaries. Descriptive methodology has been adopted to include all staff who are working at Directorate of Culture in Latakia province libraries, amounting to almost (154) employees, due to the small size of the research population. Comprehensive survey has been used, it was distributed to (154) workers, a (141) questionnaires were found suitable for analysis, and the response rate was (91.56%). The research found the following results:*There is positive and significant relationship between workers commitment to workers values and ethic and the promotion of public libraries between user, where (66.3%) of the developments in the promotion of the activities of public libraries between audience beneficiaries changes interpreted by employees to the values and work ethic commitment.*There is positive and significant relationship between confidence and strengthen the relationship between the public library community and the promotion of activities between the public beneficiaries building, where (57.2%) of the developments in the promotion of the activities of public libraries between audience beneficiaries changes interpreted build confidence and strengthen the relationship with the library community.*There is positive and significant relationship between the network of social relations in public libraries development and promotion of activities between the public beneficiaries relationship, where that (52.3%) of the developments in the promotion of the activities of public libraries between audience beneficiaries changes interpret the development of the network of social relations.*There is positive and significant relationship between the investment public library potential development to improve community services and the promotion of activities between the public beneficiaries, where that (49.1%) of the developments in the promotion of the activities of public libraries between audience beneficiaries changes interpreted Investment Public Library potential for improving community services development.